Implementation Of Early Warning Score By Healthcare Workers In Primary Care To Prevent The Deterioration Of Catastrophic Diseases - Sigalingging, Yulia Emma Wahyu Kristi Astuti (Jurnal FARMASIMED (JFM), 2024)
Title: Implementation of Early Warning Score by Healthcare Workers in Primary Care to Prevent the Deterioration of Catastrophic Diseases Background: Catastrophic diseases, such as cardiovascular disease, stroke, and kidney failure, contribute significantly to morbidity and mortality rates worldwide. The implementation of the Early Warning Score (EWS) in primary healthcare settings plays a crucial role in the early detection of patient deterioration, allowing for timely interventions and reducing emergency referrals. Objective: This study aims to analyze the implementation of EWS by healthcare workers in primary care, assess its effectiveness in preventing disease deterioration, identify challenges faced during implementation, and provide recommendations for optimizing EWS utilization. Methodology: This research employs a mixed-method approach (quantitative and qualitative) with a descriptive-analytical design. Data collection methods include questionnaires, direct observations, in-depth interviews, and medical record analysis. The study involves healthcare workers (doctors, nurses, and midwives) in primary healthcare facilities that have adopted EWS. Quantitative data were analyzed using statistical methods, while qualitative data were processed using thematic analysis. Results: The findings indicate that EWS is effective in early detection of patient deterioration, reducing emergency referrals by approximately 30%. Most healthcare workers demonstrated a good understanding of EWS, but challenges remain, including lack of training, limited resources, and inconsistent adherence to EWS protocols. Healthcare workers reported that EWS improved patient monitoring and decision-making processes, contributing to better patient outcomes. Conclusion: The implementation of EWS in primary healthcare significantly enhances patient safety, early detection, and timely intervention, ultimately preventing the worsening of catastrophic diseases. However, successful implementation requires adequate training, sufficient medical equipment, and strong institutional support. Strengthening EWS utilization in primary care can improve health service quality and reduce complications associated with catastrophic diseases